Increased endothelin‐1‐mediated vasoconstriction after organ culture in rat and pig ocular arteries can be suppressed with MEK/ERK1/2 inhibitors. Issue 5 (25th January 2018) - Blixt, Frank W.; Haanes, Kristian Agmund; Ohlsson, Lena; Tolstrup Christiansen, Anders; Warfvinge, Karin; Edvinsson, Lars
Abstract: Purpose: Even though retinal vascular changes following ischaemia have been poorly understood, the upregulation of vasoconstrictive endothelin‐1 (ET‐1) receptors (ETA /ETB ) following global cerebral ischaemia has been described. The aim of this study was to investigate whether or not the MEK/ERK1/2 pathway is involved in the observed upregulation and whether specific MEK/ERK1/2 inhibitors U0126 and trametinib can prevent it. Methods: The aim was also to localize ETA and ETB receptors using immunohistochemistry in both fresh rat ophthalmic arteries and after 24‐hr organ culture and study the receptors functionally using myography. Pig retinal arteries also underwent 24‐hr organ culture to validate similar responses across species and the retinal vasculature. Results: Results showed that following organ culture there is a significant increase in ET‐1‐mediated vasoconstriction, in particular via the ETB receptor. Furthermore, immunohistochemistry revealed a clear increase in pERK in the smooth muscle cells of rat ophthalmic artery. U0126 and trametinib were successful in attenuating the functional vasoconstriction in both rat and pig, as well as restoring immunofluorescence of pERK to fresh levels and counteracting ETB expression in the smooth muscle cells of the rat ophthalmic artery. Conclusion: This is the first study to show that the MEK/ERK1/2 pathway in responsible for the increase in functional vasoconstriction via ET‐1 receptor in rat ophthalmic and pig retinal arteries. Furthermore, this study is the first to suggest a way of inhibiting and preventing such an increase. With these results, we suggest a novel approach in retinal ischaemia therapy.